Food pricing strategies, population diets, and non-communicable disease: a systematic review of simulation studies. - Helen Eyles; Cliona Ni Mhurchu; Nhung Nghiem; Tony Blakely (PLoS Medicine, 2012)
Background Food pricing strategies have been proposed to encourage healthy eating habits, which may in turn help stem global increases in non-communicable diseases. This systematic review of simulation studies investigates the estimated association between food pricing strategies and changes in food purchases or intakes (consumption) (objective 1); Health and disease outcomes (objective 2), and whether there are any differences in these outcomes by socio-economic group (objective 3). Methods and findings Electronic databases, Internet search engines, and bibliographies of included studies were searched for articles published in English between 1 January 1990 and 24 October 2011 for countries in the Organisation for Economic Co-operation and Development. Where ≥ 3 studies examined the same pricing strategy and consumption (purchases or intake) or health outcome, results were pooled, and a mean own-price elasticity (own-PE) estimated (the own-PE represents the change in demand with a 1% change in price of that good). Objective 1: pooled estimates were possible for the following: (1) taxes on carbonated soft drinks: own-PE (n  =  4 studies), -0.93 (range, -0.06, -2.43), and a modelled -0.02% (-0.01%, -0.04%) reduction in energy (calorie) intake for each 1% price increase (n  =  3 studies); (2) taxes on saturated fat: -0.02% (-0.01%, -0.04%) reduction in energy intake from saturated fat per 1% price increase (n  =  5 studies); and (3) subsidies on fruits and vegetables: own-PE (n = 3 studies), -0.35 (-0.21, -0.77). Objectives 2 and 3: variability of food pricing strategies and outcomes prevented pooled analyses, although higher quality studies suggested unintended compensatory purchasing that could result in overall effects being counter to health. Eleven of 14 studies evaluating lower socio-economic groups estimated that food pricing strategies would be associated with pro-health outcomes. Food pricing strategies also have the potential to reduce disparities. Conclusions Based on modelling studies, taxes on carbonated drinks and saturated fat and subsidies on fruits and vegetables would be associated with beneficial dietary change, with the potential for improved health. Additional research into possible compensatory purchasing and population health outcomes is needed.